Traditional Asian Herbs in Skin Whitening: The Current Development and Limitations - Hu, Yibo; Zeng, Hongliang; Huang, Jinhua; Jiang, Ling; Chen, Jing; Zeng, Qinghai (Frontiers in Pharmacology, 2020)
In Asia, the market for whitening cosmetics is expanding rapidly, more and more people prefer to use natural products. Driven by natural product demand and technical advances, herbal research is also developing fast. Lots of studies reported that Asian herbal reagents can reduce melanogenesis, these findings provide evidence for the whitening application of Asian herbs. However, the current development status and challenges of herbal research need attention too. By reviewing these studies, different problems in studying herbal formulas, extracts, and active ingredients were presented. One of the most influential troubles is that the components of herbs are too complex to obtain reliable results. Thus, an understanding of the overall quality of herbal research is necessary. Further, 90 most cited Asian herbal studies on whitening were collected, which were conducted between 2017 and 2020, then statistical analysis was carried out. This work provided a comprehensive understanding of Asian herbal research in skin whitening, including the overall status and quality, as well as the focuses and limitations of these studies. By proactively confronting and analyzing these issues, it is suggested that the focus of herbal medicine research needs to shift from quantity to quality, and the new stage of development should emphasize transformation from research findings to whitening products.